Imagini ale alterității în proza feminină contemporană / IMAGES OF ALTERITY IN THE CONTEMPORARY FEMININE PROSE - Alina Bako (Incursiuni în imaginar)
Contemporary women’s prose writing has evolved along two distinct directions: on the one hand, the recollection of a recent past, carrying documentary, historical touches, a past linked to the communist age of the contemporary Romanian society, and, on the other hand, by a palatable return to the Phanariot era, with the help of an innovative linguistic and cultural reference. We are talking here about Doina Ruști’s novel Mâța Vinerii published in 2017, which outlines a Balkan-Oriental atmosphere. The images of otherness are built on a number of levels on which multiculturality elements are overlapping: the Turk (Ismail Bina), the Greek (Costas), the Romanian (Caterina Greceanu), the Gypsy (Silică the cook), the French (Dubois). Seen through the female character’s eyes, a woman seemingly descending from the Homeric line of Circe the witch or from the picturesque description of Saint Augustine or of Thomas Aquinas, the others become magic formulae of analysis, an imagological exercise of defining the communities that they illustrate. Another form of alterity is analyzed at the second tier of the narrative, which, beyond the historical descriptions, is refined by the choice of “magic formulae”, the witch’s butter or ova mora and which test the linguistic inventiveness, becoming an occasion for the insertion of the fantastic in the narrative, through the use of magic. The little witch is different from the others, and Sator’s discovery proposes a third dimension of alterity.